Evaluation of students’ dietary behaviours depending on gender - Daniuseviciute-Brazaite, Laura; Abromaitiene, Laima (Progress in Nutrition, 2018)
It is believed that university students commit many nutritional errors due to changes in lifestyle such as moving away from the family home, irregular meals, long hours spent studying, and frequently taking part-time jobs. Thus, we aimed to a) describe the baseline dietary intake of university students, b) identify differences in healthy eating between genders, and c) explore the relationship between lipoproteins and anthropometric data. In total, 500 students, 339 females and 161 males from Lithuanian universities and colleges participated in the study. The Food Frequency Questionnaire was used to evaluate dietary habits. The body composition values and blood analysis were estimated. Most participants (74.3%) reported regularly eating breakfast on weekdays, but of those, less than half ate breakfast 1-2 days a week. Females were more likely to consume cooked vegetables, salad/raw vegetables, fresh fruits, and curd-/cream cheese/yoghurt (p